Poetic Industry: The Modernity of the Rhyming Weavers - Charles I. Armstrong (Review of Irish Studies in Europe, 2018)
The so-called “Rhyming Weavers” were artisan poets, mainly writing in the 18th and 19th centuries. John Hewitt’s Rhyming Weavers & Other Country Poets of Antrim and Down (1974) has played a crucial role in defining this group of writers, both in terms of who they were – Ulster-Scots poets of a particular region in the North of Ireland – and with respect to their achievement. This paper addresses the modernity of the Weaver poets, countering a tendency to see their work as merely nostalgic or belated manifestations of pre-modernist belonging and harmony. The singular dimension given to the work of the Rhyming Weavers by the combination of the vocations of writer and weaver is scrutinized, as close readings show how poems by James Orr, Thomas Beggs, and David Herbison self-reflectively engage with the mechanization of the textile industry.